2017
DOI: 10.1063/1.5003800
|View full text |Cite
|
Sign up to set email alerts
|

Optimized mid-infrared thermal emitters for applications in aircraft countermeasures

Abstract: We introduce an optimized aperiodic multilayer structure capable of broad angle and high temperature thermal emission over the 3 μm to 5 μm atmospheric transmission band. This aperiodic multilayer structure composed of alternating layers of silicon carbide and graphite on top of a tungsten substrate exhibits near maximal emittance in a 2 μm wavelength range centered in the mid-wavelength infrared band traditionally utilized for atmospheric transmission. We optimize the layer thicknesses using a hybrid optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The well‐known example is the case of 1D photonic crystals (they can be treated as unpatterned metasurfaces) that their optical responses can be quantitatively calculated by the transfer matrix method . As a result, many optimization methods for these structures are proposed and the robustness of this kind of structures shows great advances over their patterned counterparts . Although previous works demonstrated that some patterned metasurfaces can be well described by a mathematical model, the conclusion is drawn by retrieval methods that cannot be employed for inverse designs directly …”
Section: Introductionmentioning
confidence: 99%
“…The well‐known example is the case of 1D photonic crystals (they can be treated as unpatterned metasurfaces) that their optical responses can be quantitatively calculated by the transfer matrix method . As a result, many optimization methods for these structures are proposed and the robustness of this kind of structures shows great advances over their patterned counterparts . Although previous works demonstrated that some patterned metasurfaces can be well described by a mathematical model, the conclusion is drawn by retrieval methods that cannot be employed for inverse designs directly …”
Section: Introductionmentioning
confidence: 99%
“…Additional applications of the presented MIR emitters/absorbers worth mentioning here are beyond analytical scenarios and go beyond the scope of the present review, e.g., among others in military for stealth technology and thermovoltaics [ 3 , 104 , 105 ], and for power generation scenarios [ 44 , 56 , 106 , 107 ].…”
Section: Selected Applicationsmentioning
confidence: 99%
“…When illuminating samples with MIR radiation, fundamental rotational and vibrational resonances within virtually any kind of molecule—with few exceptions—independent of molecular weight, complexity, dimension, physical status (i.e., gas, liquid, semi-solid, solid) or nature (i.e., organic and inorganic) are excited. Hence, the MIR spectrum of a sample is frequently referred to as the ‘molecular fingerprint’ enabling the detection and quantification of a wide range of relevant molecular compounds in environmental, health and medical, industrial, and security and defense applications [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Broadband near-perfect absorbers, operating in the visible and near-infrared wavelength ranges, have been widely investigated-due to their many potential applications in chemical sensing [1]- [3], thermophotovoltaic energy conversion [4], [5], imaging [6], color filters [7], [8], and thermal emitters [9]- [13]. Broadband near-perfect absorption requires almost perfect impedance matching between the structure and air over a broad wavelength range [14]- [16].…”
Section: Introductionmentioning
confidence: 99%